2021
DOI: 10.1080/07391102.2021.1969280
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic characterization, antimicrobial activity, molecular docking and DFT studies of proton transfer (H-bonded) complex of 8-aminoquinoline (donor) with chloranilic acid (acceptor)

Abstract: Figure S1. Expanded FTIR of the CT Supplementary InformationSynthesis, Spectroscopic characterization, antimicrobial activity, molecular docking and DFT studies of proton transfer (H-bonded) complex of 8-aminoquinoline (donor) with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…H-bonding is a notable indicator of strong protein–ligand interactions, and it commonly results in high binding affinity [ 51 ]. In protein–ligand interactions, the number of hydrogen bonds often increases the inhibitor potency against the target protein.…”
Section: Resultsmentioning
confidence: 99%
“…H-bonding is a notable indicator of strong protein–ligand interactions, and it commonly results in high binding affinity [ 51 ]. In protein–ligand interactions, the number of hydrogen bonds often increases the inhibitor potency against the target protein.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Leu325, Ala321, Ala108, and Ala176 established π-alkyl interactions while Asp172 formed a halogen (fluorine) interaction [ 27 , 28 ]. The best-docked pose of [(Ris) (PA)]-dopamine revealed that the amino acid residues, including Thr142, Ala185, His393, and Tyr408, formed hydrogen bond interactions, Val115 and Phe389 established π-alkyl interactions, Trp386 established π-sigma, and Cys118 formed a halogen (fluorine) interaction [ 29 , 30 ]. The best-docked pose of the [(Ris) (PA)]-adrenergic receptor interaction revealed that the amino acid residues Val414, Asp206, Asp131, and Ser218 formed hydrogen bond interactions, while Phe398, Phe423, and Cys135 established π-alkyl interactions, and Val132 and Ser214 established π-sigma and halogen (fluorine) interactions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The [(SRX)(TCNQ)]-dopamine (CTcD) shows that the amino acid residues, including Tyr416 and Trp413, formed hydrogen bond interactions ( Figure 8 a). There are other interactions between Leu94, Trp100 (π-Alkyl), Phe189 (π-Sigma), Asp114 (π-Anion), and Ile184 (halogen-fluorine) [ 59 ]. The theoretical binding energies of SRX with the serotonin, dopamine and TrkB kinase receptors were −7.3, −7.4, and −6.0 kcal/mol, respectively, after molecular docking.…”
Section: Resultsmentioning
confidence: 99%